Moving pictures - Immonen, Kathryn; Immonen, Stuart (Atlanta, Ga. Top Shelf Productions, 2010)
"Moving Pictures is the story of the awkward and dangerous relationship between curator Ila Gardner and officer Rolf Hauptmann, as they are forced by circumstances to play out their private lives in a public power struggle. The narrative unfolds along two time lines which collide with the revelation of a terrible secret, an enigmatic decision that not many would make, and the realization that sometimes the only choice left is the refusal to choose.
Keywords: Art museum curators -- Comic books, strips, etc; Nazis -- Comic books, strips, etc; World War, 1939-1945 -- Europe -- Comic books, strips, etc